White racism, civility, and the obligations of the socially privileged. Issue 3 (20th July 2020) - Andolsen, Barbara Hilkert
Abstract: Civility is a virtue associated with civic life, particularly with politics. This article briefly discusses civility as a moral principle requiring moral actions that give rise to the virtue of civility. Civility requires different practices on the part of persons with differential access to social power. In a white supremacist society, those with white privilege must avoid the temptation to use accusations of incivility to silence black voices. Suggestions are offered about how those with white privilege can fulfill their particular duties of civility in a racist society. Points include listening to hard truths and resisting retreat into white fragility.